Descriptive Study of Knowledge Level, Socio-Economic, Patterns Feeding, Education Level in Mothers of Toddlers With Stunting at South Purwokerto Health Center Banyumas Regency - Khbobibah Khobibah; Elisa Ulfiana; Riyanti Riyanti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2022)
The problem of stunting is a major nutritional problem in Indonesia. Data from Monitoring Nutritional Status, Stunting has the highest prevalence compared to other nutritional problems. The prevalence of short toddlers has increased from 27.5% in 2016 to 29.6% in 2017. Community nutrition problems can have an impact on the level of health and life expectancy which are one of the main elements in determining the success of development (Purba, 2019). The purpose of this study was to describe the level of socio-economic knowledge, feeding patterns, education level of mothers with stunting toddlers at the South Purwokerto Health Center, Banyumas Regency. This research uses a quantitative type. The technique in taking samples is simple random sampling. The sample in the study was 136 mothers under five. The instrument used by the questionnaire researcher has been tested for validity. The results of this study indicate that respondents have knowledge, most of the respondents have high knowledge, as many as 74 respondents (54.4%) and there are 38 respondents (27.9%) who have low knowledge. %) and 56 respondents (41.2%) had high socio-economic, the pattern of feeding most of the respondents had the right pattern of feeding as many as 93 respondents (68.4%) and 43 respondents (31.6%) had an inappropriate feeding pattern, Description Secondary education level (SMA, MA) as many as 82 respondents (60.3%) and 20 respondents (14.7) have higher education (D3 and Bachelor)